I survived the Joplin tornado, 2011 - Tarshis, Lauren; Dawson, Scott (New York Scholastic Press, 2015)
When eleven-year-old Dex goes storm chasing with Dr. Norman Gage, they get caught in the path of a tornado and Dex must find bravery within himself to survive.
M
Includes bibliographical references.
b
b
Accelerated Reader AR
Accelerated Reader AR
Keywords: Storm chasers -- Fiction; Tornadoes -- Missouri -- Joplin -- Fiction; Survival -- Fiction; Missouri -- Fiction